Studi Pengurangan Cemaran Gas Buang Sulfur Dioksida (So2) dari Emisi Cerobong Pabrik Nikel dengan Menggunakan Senyawa Kimia Penjerapamonium Hidroksida - Agus Dina; M. Sjahrul; Muhammad Zakir; Dadang Dadang (Al-Kimia, 2016)
Research on absorption of gaseous SO2 from factory emissions of nickel ore industry using solution of ammonium hydroxide has been done. Research conducted with variations including concentration, temperature, and time of contact. Variation of the concentration used were 1%, 2%, 3%, 4% and 5%; while variations of the temperature  used were 20oC, 25oC, 30oC, 35oC, and 40oC; and the contact time were 10, 15, 20, 25 and 30 minutes. SO2 gas emissions sampling is done at a time when the factory operates at flow velocity and temperature conditions exhaust gas emissions. Results showed the greater concentration of the solution absorbing the greater the concentration of sulfur dioxide gas absorption, absorption temperature range between 30° C-40° C, and the longer the absorption of the greater number of SO2 absorption. A comparison of the percentage of the results of the average accumulation of absorption between absorbent solution (ammonium hydroxide) and slurry of calcium carbonate to reduce sulfur dioxide emissions to ambient air showed results still under the limestone slurry i.e. absorption capability comparison 95.00%: 62,91%. Difference in SO2 gas that is not absorbed out as emissions are still on top of the raw set quality standard (750 mg/m3). The gas is absorbed to form ammonium sulphate compounds that could be accommodated and packaged for commercialized as a by-product in the form of inorganic fertilizers valued economically. As such, ammonium hydroxide is used as an alternative to allow compound absorbent and produces no side residue so that the result is considered safe for the environment.